Numerical Modeling of Kutaisi City Atmospheric Air Pollution with PM2.5 Particles in Winter During Ground Level Calm and Background Eastern Wind in the Free Atmosphere - Surmava, Aleksandre A.; Kukhalashvili, Vepkhia G.; Gigauri, Natia G.; Intskirveli, Liana N.; Gverdtsiteli, Leila V. (Journals of Georgian Geophysical Society, 2025)
Spatial distribution and time change of PM2.5 particles dissipated in the atmosphere as a result of motor transport traffic in Kutaisi city has been studied using computer modeling. This modeling has been made through combined integration of equations of time evolution of meso-scale atmospheric processes and admixtures’ transfer-diffusion, using the relevant initial and boundary conditions. Such meteorological situation has been considered, during which wind velocity in surface layer of the atmosphere equal to 0, while there is background eastern wind in the free atmosphere. Atmospheric pollution is caused by microparticles dissipated in the air during motor transport traffic. The wind fields formed in boundary layer of the atmosphere resulting from interaction of terrain and background flows in winter and fields of concentrations of microparticles transferred by wind and dissipated in the air at different heights from the earth ground have been plotted using numerical modeling data. Areas of relatively severe and mild contamination have been determined, peculiarities of vertical distribution of concentrations have been analyzed. It has been showed that the shapes of vertical distribution of concentrations in surface layer of the atmosphere are similar of temperature distributions in to dry thermals.